Secondary battery

By mixing olivine structural material into the positive electrode material of the ternary system secondary battery and introducing two-stage discharge voltage platforms, the thermal runaway problem of secondary battery at high temperatures and excessive discharge is solved, and the safety performance of the battery is significantly improved.

CN119864385APending Publication Date: 2025-04-22ENVISION AESC JAPAN LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311373366.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The safety performance of existing ternary secondary batteries is poor, especially at high temperatures and excessive discharge, there is a risk of thermal runaway.

Method used

The olivine structural material is mixed into the positive electrode material mainly composed of layered structural materials, and two stages of discharge voltage platforms are introduced to reduce the discharge depth of the layered structural material and improve the structural thermal stability of the positive electrode material.

Benefits of technology

By introducing the second voltage platform, the discharge depth of the battery under the high voltage platform is reduced, the thermal stability of the secondary battery is improved, thermal runaway is prevented, and the safety performance of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864385A_ABST
    Figure CN119864385A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery, and belongs to the technical field of secondary batteries, the secondary battery comprises a positive pole piece, a diaphragm and a negative pole piece, the positive pole piece comprises a positive pole material, the positive pole material comprises a first active substance and a second active substance, the first active substance is a layered structure material; the second active substance is an olivine structure material; the mass ratio of the second active substance to the sum of the mass of the first active substance and the second active substance is 5-30wt%; a discharge curve of the secondary battery has a first voltage platform and a second voltage platform. According to the secondary battery disclosed by the invention, the layered structure material and the olivine structure material are mixed in the positive electrode material, so that the thermal stability of the secondary battery can be improved while the voltage and the capacity of the secondary battery are considered, thermal runaway caused by excessive charging and discharging of the layered active substance is prevented, and the safety performance of the secondary battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a secondary battery. Background Art

[0002] Electrochemical devices (e.g., lithium-ion batteries) have entered our daily lives with the advancement of science and technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their safety performance has attracted more and more attention, especially the continued fermentation of some electric vehicle combustion and explosion incidents, which has led to new requirements for the safety performance of lithium-ion batteries by users, after-sales service and lithium-ion battery manufacturers. In response to this, the country has also introduced more stringent laws and regulations. Based on the current safety status of lithium batteries, it is necessary to make some improved designs for the safety of lithium batteries.

[0003] At present, ternary materials, as positive electrode materials for lithium-ion batteries, have outstanding advantages such as high energy density, high voltage platform, ideal crystal structure, low self-discharge and no memory effect. They are now widely used in lithium-ion batteries, but their high-temperature performance has defects, and their rate performance and structural stability are not as good as lithium iron phosphate. Compared with lithium iron phosphate lithium-ion batteries, the ternary material lithium-ion batteries made from them have poor high-temperature performance, cycle performance and structural stability.

[0004] Therefore, it is necessary to design a secondary battery that can improve the safety performance of batteries using ternary materials as the main positive electrode material to solve the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides a secondary battery to solve the technical problem that the existing ternary system secondary batteries have poor safety performance.

[0006] To achieve the above-mentioned object and other related objects, the present invention provides a secondary battery, the secondary battery comprising a positive electrode sheet, a separator and a negative electrode sheet, the positive electrode sheet comprising a positive electrode material, the positive electrode material comprising a first active substance and a second active substance;

[0007] Wherein, the first active material is a layered structure material; the second active material is an olivine structure material; the mass ratio of the second active material to the sum of the mass of the first active material and the second active material is 5-30wt%; the discharge curve of the secondary battery has a first voltage platform and a second voltage platform, and the measured voltage y of the secondary battery satisfies the relationship y1 min <y<y1 max or y2 min <y<y2 max , y1 and y2 satisfy equations (1) and (2):

[0008] y1=0.5265a+d (1)

[0009] y2=-0.5265b+c (2)

[0010] Among them, a is the mass ratio of the first active substance to the sum of the masses of the first active substance and the second active substance, b is the mass ratio of the second active substance to the sum of the masses of the first active substance and the second active substance, c is the first voltage platform for the first active substance to participate in discharge, and the first voltage platform is 3.7143~3.7743V, d is the second voltage platform for the second active substance to participate in discharge, and the second voltage platform is 3.1878~3.2478V.

[0011] In an example of the present invention, the proportion of the curve of the second active material participating in the discharge in the discharge curve is 80% to 87% of the mass proportion b.

[0012] In an example of the present invention, the curve in which the second active material participates in the discharge accounts for 4% to 25%.

[0013] In one example of the present invention, the layered structure material is LiNi x Co y M 1-x-y O2, wherein 0<x<1, 0<y<1, and the M element includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga and Ta.

[0014] In one example of the present invention, the olivine structural material is LiFe z G 1-z PO4, wherein 0<z<1, and the G element includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga and Ta.

[0015] In an example of the present invention, the average particle size D50 of the first active material is 0.5-5 μm, and the average particle size D50 of the second active material is 0.3-3 μm.

[0016] In an example of the present invention, the first active material is single crystal and / or polycrystalline.

[0017] In an example of the present invention, the orientation degree of the positive electrode sheet is 70-99; the orientation degree of the negative electrode sheet is 10-60.

[0018] In one example of the present invention, the compaction density of the positive electrode sheet is 3.0-3.6 g / cm 3 The surface density of the positive electrode sheet coated on one side is 0.014-0.02 g / cm2 .

[0019] In one example of the present invention, the compaction density of the negative electrode plate is 1.1 to 1.7 g / cm 3 The surface density of the negative electrode sheet coated on one side is 0.008 to 0.013 g / cm 2 .

[0020] The secondary battery of the present invention introduces two discharge voltage platforms during the discharge process of the secondary battery by mixing olivine structure materials into the positive electrode materials mainly composed of layered structure materials, so that the secondary battery can be discharged from the higher first voltage platform to the lower second voltage platform during discharge, thereby reducing the discharge depth of the layered structure material while taking into account the voltage and capacity of the secondary battery, improving the thermal stability of the secondary battery, preventing the battery from thermal runaway during overcharge and discharge, and thus improving the safety performance of the secondary battery. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A discharge curve test diagram of a secondary battery in some embodiments of the present invention;

[0023] Figure 2 is a graph showing the relationship between the measured voltage of a secondary battery and the mass percentage of the first active material in some embodiments of the present invention;

[0024] Figure 3 is a graph showing the relationship between the measured voltage of a secondary battery and the mass percentage of the second active material in some embodiments of the present invention;

[0025] Figure 4 This is an XRD test diagram of a positive electrode sheet of a secondary battery in one embodiment of the present invention;

[0026] Figure 5 This is an XRD test diagram of the negative electrode sheet of a secondary battery in one embodiment of the present invention. DETAILED DESCRIPTION

[0027] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0028] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0029] The inventors have found that secondary batteries using ternary layered materials as positive electrode materials have advantages such as high energy density and high discharge voltage platform, but due to the poor thermal stability of ternary materials, the safety performance of secondary batteries has hidden dangers. Specifically, during the high voltage over-discharge process, Ni in the ternary material 4+ ions are reduced to Ni 2+ , while maintaining charge neutrality O 2- Oxidized oxygen escapes from the lattice, and as a large amount of oxygen escapes, a large number of oxygen vacancies are generated, thereby reducing the activation energy barrier for the migration of transition metal cations and accelerating the phase change process of the material from layered structure to spinel structure and rock salt phase structure. The release of oxygen and the structural degradation of the positive electrode material form a vicious circle, affecting the thermal runaway temperature of the battery, resulting in a decrease in the thermal stability of the battery, which in turn causes safety risks.

[0030] It can be seen that if the positive electrode material is at a relatively high discharge voltage platform for a long time during the discharge process, the irreversible structural collapse of the layered structure material will be aggravated. The layered structure material will produce a large amount of gas and reduce the activation energy barrier as the structure collapses, which causes the layered structure of the positive electrode material to continue to collapse during the discharge process, and then leads to a rapid drop in the thermal runaway temperature of the battery.

[0031] Therefore, in order to solve the above problems, the present invention provides a secondary battery, which mixes olivine structural materials into positive electrode materials mainly composed of layered structural materials. The olivine structural materials mixed into the layered structural materials are used to introduce two discharge voltage platforms during the discharge process while taking into account the storage voltage capacity of the secondary battery. When discharging, the secondary battery can transition from a higher first voltage platform to a lower second voltage platform, which effectively reduces the discharge depth of the layered structural material under the high voltage platform, improves the structural thermal stability of the positive electrode material, and prevents the thermal runaway temperature of the battery from dropping rapidly with excessive discharge.

[0032] The present invention provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, an electrolyte, a diaphragm, and corresponding connecting accessories and circuits. Among them, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode material. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, and the negative electrode active material layer includes a negative electrode material, wherein the negative electrode material can be a carbon-based material (such as graphite, hard carbon or soft carbon), a silicon-based material (such as silicon oxide) or a carbon-silicon composite material. In the secondary battery, the positive and negative electrode materials can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive electrode plate and the negative electrode plate, and the diaphragm can pass lithium ions but is not conductive, thereby separating the positive electrode plate and the negative electrode plate to prevent short circuit. The positive electrode material and the negative electrode material usually play a decisive role in the key performance factors such as the energy storage function of the lithium battery, the energy density of its battery cell, the cycle performance and safety.

[0033] In the secondary battery, the positive electrode material includes a first active material and a second active material, the first active material is a layered structure material, such as lithium cobalt oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, and the second active material is an olivine structure material, such as lithium iron phosphate or lithium iron manganese phosphate. In the positive electrode material, the mass proportion of the first active material relative to the total mass of the first active material and the second active material is 70-95wt%, and the mass proportion of the second active material relative to the total mass of the first active material and the second active material is 5-30wt%. For example, in some embodiments, the mass proportion of the first active material is 95wt%, 90wt%, 85wt%, 80wt%, 75wt% or 70wt%, and correspondingly, the mass proportion of the second active material is 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.

[0034] In the present application, the first active material and the second active material may further contain non-metallic elements, for example, the non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur, which can further improve the stability of the positive electrode active material.

[0035] It should be noted that the material form of the first active substance is not limited. For example, the first active substance may be single crystal, polycrystalline, or a mixture of single crystal and polycrystalline. In some embodiments, the first active substance is polycrystalline.

[0036] like Figures 1 to 3 As shown in the figure, since the positive electrode material of the secondary battery contains layered structure materials and olivine structure materials, the secondary battery discharge curve has a first voltage platform with a higher voltage and a second voltage platform with a lower voltage. The measured voltage y during the discharge process of the secondary battery is between the first voltage platform and the second voltage platform. The measured voltage is the working voltage during the discharge process of the secondary battery, which usually refers to the potential difference between the positive and negative electrodes of the battery under normal working conditions. Specifically, the measured voltage y of the secondary battery satisfies the relationship y1 min <y<y1 max or y2 min <y<y2 max , y1 and y2 satisfy equations (1) and (2):

[0037] y1=0.5265a+d (1)

[0038] y2=-0.5265b+c (2)

[0039] Among them, a is the mass ratio of the first active substance to the sum of the masses of the first active substance and the second active substance, b is the mass ratio of the second active substance to the sum of the masses of the first active substance and the second active substance, c is the first voltage platform for the first active substance to participate in discharge, and the first voltage platform is 3.7143~3.7743V, d is the second voltage platform for the second active substance to participate in discharge, and the second voltage platform is 3.1878~3.2478V.

[0040] Specifically, Figure 2 and Figure 3 As shown, the measured voltage y of the secondary battery satisfies y1 min <y<y1 max , where y1 min =0.5265a+3.1878,y1 max =0.5265a+3.2478; or the measured voltage y of the secondary battery satisfies y2 min <y<y2 max , where y2 min =-0.5265b+3.7143,y2 max =-0.5265b+3.7743.

[0041] like Figures 1 to 3As shown, the mixed layered structure material and olivine structure material in the positive electrode material introduce the first voltage platform and the second voltage platform during the discharge process of the secondary battery, while also ensuring that the measured voltage of the secondary battery will not decay excessively. The measured voltage of the secondary battery discharge is maintained at 3.55 to 3.75 V based on the change of the mass proportion b of the second active material. For example, when the mass proportion of the second active material relative to the sum of the mass of the first active material and the second active material in the positive electrode material is 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%, the measured voltage of the secondary battery discharge corresponds to 3.72V, 3.70V, 3.68V, 3.66V, 3.63V or 3.61V, respectively. In this operating voltage range, the secondary battery can still maintain a high discharge efficiency.

[0042] like Figures 1 to 3 As shown, in the discharge curve of the secondary battery, the proportion of the introduced second voltage platform in the curve is positively correlated with the mass content of the olivine structure material mixed in the positive electrode material. In some embodiments, the proportion of the curve in which the second active substance participates in the discharge curve is 80% to 87% of the mass proportion b of the second active substance. For example, in some examples, when the mass proportion b of the second active substance in the positive electrode material is 5 to 30wt%, the proportion of the curve in which the second active substance participates in the discharge is 4% to 25%. In the secondary battery, the higher the mass proportion of the olivine structure material mixed in the positive electrode material, the higher the discharge depth of the second voltage platform in the discharge curve, and the thermal runaway temperature of the secondary battery also increases accordingly, and the thermal stability of the battery can be significantly improved.

[0043] In some embodiments, the layered structure material is LiNi x Co y M 1-x-y O2, wherein 0<x<1, 0<y<1. In some embodiments, the M element is selected from one or more combinations of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga and Ta. That is, the M element can be any one of the element types listed above, such as Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga or Ta, etc.; the M element can also be any two or more combinations of the element types listed above, for example, the M element is a combination of Mn and Zr, or a combination of Mn and Mg, or a combination of Al and Ti, or a combination of Al and Zn, or a combination of Mn, Al and Ga, or a combination of Mn, Al, Cu and Mg, etc., which are not listed one by one here.

[0044] Olivine structural material is LiFe z G 1-zPO4, wherein 0<z<1. In some embodiments, the G element is selected from one or more combinations of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga and Ta. That is, the G element can be any one of the element types listed above, such as Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga or Ta, etc.; the G element can also be any two or more combinations of the element types listed above, for example, the G element is a combination of Mn and Zr, or a combination of Mn and Mg, or a combination of Al and Ti, or a combination of Al and Zn, or a combination of Mn, Al and Ga, or a combination of Mn, Al, Cu and Mg, etc., which are not listed one by one here.

[0045] In addition, when the M element and the G element are two or more combinations, there is no restriction on the ratio of each element in the combination, and they can be mixed in any ratio, etc. In other embodiments, the M element and the G element can also be element types not listed above.

[0046] In some embodiments, the average particle size D50 of the first active substance is 0.5 to 5 μm, for example, the average particle size D50 of the first active substance may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm; the average particle size D50 of the second active substance is 0.3 to 3 μm, for example, the average particle size D50 of the second active substance may be 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, 2.3 μm, 2.5 μm, 2.7 μm or 3 μm.

[0047] Among them, within the above-mentioned particle size range, the particle size distributions of the first active substance and the second active substance overlap with each other, the positive electrode material has good uniformity after the first active substance and the second active substance are mixed and rolled, and the contact interface of the first active substance and the second active substance mixed in the positive electrode material has good affinity, which can improve the structural stability of the positive electrode material while ensuring the conductive efficiency of the positive electrode material, thereby improving the thermal safety performance of the secondary battery.

[0048] In some embodiments, the orientation degree of the positive electrode sheet is 70 to 99, for example, the orientation degree of the positive electrode sheet can be 70, 75, 80, 85, 90, 95 or 99. Figure 4 As shown, the orientation degree of the positive electrode piece is Qc=C003 / C110, C003 is the peak area of ​​the 003 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode piece, C110 is the peak area of ​​the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode piece, the diffraction angle range of the 003 characteristic peak is 17°~19.5°, and the diffraction angle range of the 110 characteristic diffraction peak is 65°~66.5°.

[0049] In some embodiments, the orientation degree of the negative electrode sheet may be 10 to 60, for example, the orientation degree of the negative electrode sheet may be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60. Figure 5 As shown, the orientation degree Qc ​​of the negative electrode pole piece is C004 / C110, C004 is the peak area of ​​the 004 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode pole piece, C110 is the peak area of ​​the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode pole piece, the diffraction angle range of the 004 characteristic peak is 54°~56°, and the diffraction angle range of the 110 characteristic diffraction peak is 76°~78°.

[0050] The inventors found that when the orientation degree of the positive electrode sheet is 70-99 and the orientation degree of the negative electrode sheet is 10-60, the dynamic performance of the positive and negative electrode sheets reaches the best, and lithium ions can be smoothly deintercalated from the positive and negative electrode sheets, thereby improving the charge and discharge performance, cycle performance and safety performance of the lithium-ion battery.

[0051] In the present invention, the positive electrode piece is subjected to an XRD scanning test according to the JIS K 0131-1996 standard, and the negative electrode piece is subjected to an XRD scanning test according to the JB / T4220-2011 standard. For example, an X-ray scanning is performed on the placed electrode piece at a scanning speed of (1 / 4)° / min, and a slit with a width of 0.2 mm is used to scan and receive X-ray diffraction light at different diffraction angles to obtain an X-ray spectrum of the test electrode piece. Among them, the diffraction angle range of the diffraction characteristic peak of the positive electrode piece 003 is 17° to 19.5°, and the diffraction angle range of the diffraction characteristic peak of 110 is 65° to 66.5°; the diffraction angle range of the diffraction characteristic peak of the negative electrode piece 004 is 54-56°; the diffraction angle scanning range of the diffraction characteristic peak of the negative electrode piece 110 is 76-78°.

[0052] In some embodiments, the compaction density of the positive electrode sheet is 3.0 to 3.6 g / cm 3 , for example, it can be 3.0 g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 or 3.6g / cm 3 ; The surface density of the single-sided coating of the positive electrode sheet is 0.014-0.02 g / cm 2 , for example, it can be 0.014 g / cm 2 , 0.015g / cm 2 , 0.016g / cm 2, 0.017g / cm 2 , 0.018g / cm 2 , 0.019g / cm 2 or 0.020g / cm 2 .

[0053] In some embodiments, the compaction density of the negative electrode sheet is 1.1 to 1.7 g / cm 3 , for example, it can be 1.1 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 or 1.7 g / cm 3 ; The surface density of the negative electrode single-sided coating is 0.008~0.013g / cm 2 , for example, it can be 0.008 g / cm 2 , 0.009g / cm 2 , 0.010g / cm 2 , 0.011g / cm 2 , 0.012g / cm 2 or 0.013g / cm 2 .

[0054] It should be noted that in the present invention, the compaction density and surface density of the positive electrode sheet and the negative electrode sheet are single-sided values, and the test methods can refer to the conventional test methods used by those skilled in the art. For example, the surface density of the electrode sheet is first tested, and then the compaction density of the electrode sheet is obtained by dividing the surface density by the thickness of the electrode sheet.

[0055] In addition, the inventors have found through research that when a lithium-ion battery containing a composite positive electrode material (i.e., the positive electrode material contains both the first active substance and the second active substance) meets the above multiple parameter limitation conditions, the charge and discharge performance, cycle performance and safety performance of the obtained lithium-ion battery reach the optimal state, meet the actual use needs, and have a lower use cost.

[0056] The composition and preparation method of the secondary battery provided by the present invention are described in detail below:

[0057] Preparation of positive electrode sheet: positive electrode material, conductive agent and binder are mixed in a mass ratio of (90 to 99): 1.5: 1.5, preferably 97: 1.5: 1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can be selected from at least one of the conductive materials such as Super P (carbon black), acetylene black, carbon nanotubes (CNT), graphene, nanocarbon fiber (VGCF), for example, the conductive agent is SP and CNT, and the mass ratio of SP and CNT is 1: 0.5; the binder can be selected from at least one of PVDF, PTFE and the like.

[0058] The preparation method of the positive electrode material includes the following steps:

[0059] The first active material and the second active material are uniformly mixed in a mass ratio of (70-95):(5-30) to obtain a mixture; and the mixture is rolled to obtain a positive electrode material. The first active material is a layered structure material, such as lithium cobalt oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, and the second active material is an olivine structure material, such as lithium iron phosphate or lithium iron manganese phosphate.

[0060] Preparation of negative electrode sheet: negative electrode materials such as graphite, conductive agent acetylene black, thickener CMC (sodium carboxymethyl cellulose) and binder SBR (styrene-butadiene rubber) are mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water is added, and the mixture is stirred to obtain negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes;

[0061] Preparation of diaphragm: The diaphragm is made of PE or PP porous membrane, preferably PP / PE / PP porous membrane, with a thickness of 9 μm to 18 μm, such as 9 μm, 12 μm, 16 μm or 18 μm; the air permeability is 180 s / 100 mL to 380 s / 100 mL, such as 180 s / 100 mL, 280 s / 100 mL or 380 s / 100 mL; the porosity is 30% to 50%, such as 30%, 40% or 50%.

[0062] Preparation of electrolyte: EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0063] Assemble the battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then wrap it with aluminum plastic film, inject the above-prepared electrolyte after drying, and finally prepare a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah after packaging, standing, and formation.

[0064] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0065] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.

[0066] Example 1

[0067] This embodiment provides a secondary battery, and the preparation process of the secondary battery is as follows:

[0068] (1) Preparation of positive electrode sheet: The positive electrode material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.5:1.5, and the solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the mixture is stirred under the action of a vacuum mixer until the system is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 16μm aluminum foil current collector, and the aluminum foil current collector is then dried at room temperature and transferred to an oven at 80℃~120℃ for 6h to dry, and then cold pressed and cut to obtain a positive electrode sheet.

[0069] The positive electrode material includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass ratio of b5wt%. The preparation method of the positive electrode material includes: uniformly mixing the first active material NCM and the second active material LFP in a mass ratio of 95:5 to obtain a mixture; rolling the mixture to obtain the positive electrode material.

[0070] (2) Preparation of negative electrode sheets: negative electrode material graphite, conductive agent acetylene black, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water was added, and the solid content of the slurry was adjusted to 55%, and then the mixture was fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on both sides of an 8 μm negative electrode current collector copper foil; after drying at room temperature, the mixture was transferred to an oven for drying, and then cold pressed, cut and other processes were performed to obtain a negative electrode sheet.

[0071] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0072] (4) Diaphragm preparation: The diaphragm is a 9 μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2 μm.

[0073] (5) Assembling the battery: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then, the sheet is wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of electrolyte. After standing, hot and cold pressing, formation, clamping, and capacity division, a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is finally prepared.

[0074] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0075] Example 2

[0076] This embodiment provides a secondary battery with the same system as that of the embodiment 1. The difference between this embodiment and the embodiment 1 is that the positive electrode material in the positive electrode plate includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass proportion of 10wt%.

[0077] Example 3

[0078] This embodiment provides a secondary battery with the same system as that of the embodiment 1. The difference between this embodiment and the embodiment 1 is that the positive electrode material in the positive electrode plate includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass proportion of 15wt%.

[0079] Example 3

[0080] This embodiment provides a secondary battery with the same system as that of the embodiment 1. The difference between this embodiment and the embodiment 1 is that the positive electrode material in the positive electrode plate includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass proportion of 15wt%.

[0081] Example 4

[0082] This embodiment provides a secondary battery with the same system as that of the embodiment 1. The difference between this embodiment and the embodiment 1 is that the positive electrode material in the positive electrode plate includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass proportion of 20wt%.

[0083] Example 5

[0084] This embodiment provides a secondary battery with the same system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that the positive electrode material in the positive electrode plate includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass proportion of 25wt%.

[0085] Example 6

[0086] This embodiment provides a secondary battery with the same system as that of the embodiment 1. The difference between this embodiment and the embodiment 1 is that the positive electrode material in the positive electrode plate includes lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass proportion of 30wt%.

[0087] Comparative Example 1

[0088] This comparative example provides a secondary battery with the same system as that of Example 1. The difference between this comparative example and Example 1 is that the positive electrode material only contains the first active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM), without mixing in the second active material, lithium iron phosphate (LiFePO4, LFP).

[0089] A discharge test and a needle penetration test were performed on the secondary batteries prepared by Examples 1 to 6 and Comparative Example 1 to verify the difference in safety performance of the secondary batteries provided by different Examples and Comparative Examples.

[0090] Discharge curve test:

[0091] At 25°C, the secondary battery is charged at a constant current of 0.1C to the upper cut-off voltage, and then charged at a constant voltage to a current <0.05C; then allowed to stand for 10 minutes; and then discharged at a constant current of 0.1C to the lower cut-off voltage. The discharge capacity curve at this time is the discharge curve.

[0092] Needle penetration test: Charge the secondary battery to 100% SOC, pierce the secondary battery with a Φ8mm steel needle at a speed of 25mm / s, observe for 1 hour and collect the maximum temperature of the secondary battery cell. If the secondary battery does not catch fire, it passes the needle penetration test. If the secondary battery catches fire, record the time from puncture to fire.

[0093] Measured voltage test:

[0094] Discharge the secondary battery at a standard rate of 1C, and divide the energy released by the secondary battery by its capacity to obtain the measured voltage.

[0095] The test results of the secondary batteries in Examples 1 to 6 and Comparative Example 1 are shown in Table 1.

[0096] Table 1: Test results of discharge performance and safety performance of secondary batteries in Examples 1 to 6 and Comparative Example 1

[0097]

[0098] By comparing the test results of Examples 1 to 6 and Comparative Example 1, it can be seen that mixing LFP into the positive electrode material mainly composed of NCM can effectively improve the thermal stability of the positive electrode material and significantly improve the safety performance of the secondary battery. Among them, adding LFP to the positive electrode material can introduce the second voltage platform for LFP to participate in the discharge process of the secondary battery, which effectively reduces the discharge depth of the layered structure material under the high voltage platform, improves the structural thermal stability of the positive electrode material, and prevents the thermal runaway temperature of the battery from dropping rapidly with excessive discharge, thereby significantly improving the safety performance of the secondary battery.

[0099] By comparing the test results of Examples 1 to 6, it can be seen that as the mass proportion b of LFP material added to the positive electrode material increases, the proportion of NCM participating in the discharge curve of the secondary battery decreases, the proportion of LFP participating in the discharge curve increases, and the maximum temperature during the secondary battery acupuncture process also decreases significantly. For example, when the mass proportion b of LFP material in the positive electrode material increases from 5wt% to 20wt%, the maximum temperature during the secondary battery acupuncture process decreases from 210°C to 30°C.

[0100] Moreover, it can be seen from the test results of Examples 3 to 6 that when the mass proportion b of LFP is higher than 20wt%, increasing the mass content of LFP in the positive electrode material does not significantly improve the thermal safety performance of the secondary battery, but will further reduce the measured voltage of the secondary battery during discharge. For example, when the mass proportion b of the LFP material in the positive electrode material increases from 20wt% to 30wt%, the maximum temperature of the secondary battery during the acupuncture process only decreases from 30°C to 28.5°C, while the measured voltage of the secondary battery continues to decrease from 3.66V to 3.61V. It can be seen that in the positive electrode material, the mass proportion b of the second active substance LFP is preferably 20wt%. The positive electrode material under this mass proportion ensures that the measured voltage of the secondary battery will not be significantly attenuated, so that the improvement effect of the thermal safety performance of the secondary battery is optimal.

[0101] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode material, and the positive electrode material comprises: A first active substance, wherein the first active substance is a layered structure material; A second active substance, wherein the second active substance is an olivine structure material; The mass ratio of the second active material to the sum of the mass of the first active material and the second active material is 5-30wt%; the discharge curve of the secondary battery has a first voltage platform and a second voltage platform, and the measured voltage y of the secondary battery satisfies the relationship y1 min <y<y1 max or y2 min <y<y2 max , y1 and y2 satisfy equations (1) and (2): y1=0.5265a+d (1) y2=-0.5265b+c (2) Among them, a is the mass ratio of the first active substance to the sum of the masses of the first active substance and the second active substance, b is the mass ratio of the second active substance to the sum of the masses of the first active substance and the second active substance, c is the first voltage platform for the first active substance to participate in discharge, and the first voltage platform is 3.7143~3.7743V, d is the second voltage platform for the second active substance to participate in discharge, and the second voltage platform is 3.1878~3.2478V.

2. The secondary battery according to claim 1, characterized in that: The second active material participates in the discharge curve in a curve ratio of 80% to 87% of the mass ratio b.

3. The secondary battery according to claim 2, characterized in that: The curve in which the second active material participates in discharge accounts for 4% to 25%.

4. The secondary battery according to claim 1, characterized in that: The layered structure material is LiNi x Co y M 1-x-y O2, wherein 0<x<1, 0<y<1, and the M element includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga and Ta.

5. The secondary battery according to claim 1, characterized in that: The olivine structural material is LiFe z G 1-z PO4, wherein 0<z<1, and the G element includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga and Ta.

6. The secondary battery according to claim 1, characterized in that: The average particle size D50 of the first active material is 0.5 to 5 μm, and the average particle size D50 of the second active material is 0.3 to 3 μm.

7. The secondary battery according to claim 1, characterized in that: The first active material is single crystal and / or polycrystalline.

8. The secondary battery according to claim 1, characterized in that: The orientation degree of the positive electrode sheet is 70-99; the orientation degree of the negative electrode sheet is 10-60.

9. The secondary battery according to claim 1, characterized in that: The compaction density of the positive electrode sheet is 3.0 to 3.6 g / cm 3 The surface density of the positive electrode sheet coated on one side is 0.014-0.02 g / cm 2 .

10. The secondary battery according to claim 1, characterized in that: The compaction density of the negative electrode plate is 1.1 to 1.7 g / cm 3 The surface density of the negative electrode sheet coated on one side is 0.008 to 0.013 g / cm 2 .